CHALLENGES BEFORE WOMEN LEADERS IN LOCAL SELF-GOVERNMENT - Hemamalini BV (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the barriers which the women leaders need to overcome in order to participate as leaders in the local self-governance structure and be an effective leader. Despite a legal provision to ensure the women’s representation in LGs, the sociocultural and the institutional (also political) constraints were found at work. Cultural and social norms and traditional role expectations affect W or ‘w Insider’ in two ways: through misappropriation of resources, insufficient training and lack of bureaucratic support, women’s integrity is doubted. Party tokenism, men meddling and party neglect further contribute to the issue. “There are also personal conflicts, the architecture of the home in terms of leader and manager, and economic dependence. This study notes the challenge that faces the policy when it is looking for the correct response, in the form of a policy, to the women leaders' empowerment at the local level, and the process of gender equality in the society. The results reinforce the significance of legislations, resources, capable leadership, and spreading awareness in terms of campaigns about changing people’s mindset. The role of civil society and international organisations in facilitating gender sensitive policy making and control is also addressed. In addressing these challenges to preparedness, women can play, and take up, leadership roles that help make local governance more inclusive, effective and sustainable.